Perspectives on Women's Higher Education Leadership from around the World - Karen Jones (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
At this time in world history, numerous scholars have emphasized the importance of having greater diversity in leadership, and specifically having greater representation by women in leadership. In particular, providing women with greater access to higher education-and having role models for women in higher education leadership-has a beneficial ripple effect, given that postsecondary institutions shape the lives of future generations. Individuals, nations, and the world collectively pay a price when women are not given full opportunities to develop and contribute their talents by serving on senior-level leadership teams. This Special Issue, titled "Perspectives on Women's Higher Education Leadership From Around the World," offers an array of articles that present research findings from both qualitative and quantitative studies, along with narratives and best practices gleaned from the lived experiences of women in academic leadership from countries on four continents: the United States, the United Kingdom, Australia, India, China, and Saudi Arabia. Taken together, these articles offer a helpful overview of the literature related to women in higher education leadership worldwide, thus addressing previous concerns that much of the research has too often taken a Western perspective that reflects inaccurate assumptions for other cultural contexts.